Pengalaman Personal Hygiene Pada Santri Putra Dengan Penyakit Scabies Di Pondok Pesantren Darullughah Wal Karomah Sidomukti Kraksaan Probolinggo - Khotimah, Husnul; Andayani, Sri Astutik; Maulidah, Robiyatul (Jurnal Keperawatan Profesional, 2021)
Scabies is a skin disease caused by an infestation of the sarcoptes scabie mite, which is transmitted by direct human contact and indirect human contact. The problem of santries  experiencing scabies is related to their poor personal hygiene, because each individual has different characteristics in maintaining personal hygiene. This research is qualitative research, the research subjects are male santries of junior high school and high school darullughah wal karomah sidomukti kraksaan probolinggo. data collection methods used observation, interviews, and documentation. This qualitative research with a phenomenological approach aims to obtain in-depth information about personal hygiene exsperinces of male santries in islamic boarding schools. Five participants were selected based on the research criteria and were saturated. Focusing selective analysis (the selective or high-painting approach) was used in data analysis. four themes identified in this research: 1) personal hygiene experience for santries 2) the environment around the santris 3) the impact of scabies on the santries 4) the handling of the satries in dealing wiht scabies. The results of this research indicate : 1) there is a description of how santries maintain ther personal hygiene properly in islamic boarding school, namely that clothes and toiletries are not used interchangedably 2) there is description of how the santris protect the environmennt around the santries 3)there is an illustration of the impactt that will arise when santris experience scabies. 4) there is a description of how the santris can overcome  scabies in islamic bording schools